Implementasi Media Pembelajaran oleh Guru Pendidikan Agama Islam dalam Meningkatkan Minat Belajar Siswa di SDN 2 Wakan Kecamatan Jerowaru Kabupaten Lombok Timur - Ami Pratama; Irwan Irwan; Jumu’ah Jumu’ah (Al-Munawwarah : Jurnal Pendidikan Islam, 2023)
This research is motivated by the importance of education for each individual, where in the education process there is the term learning which is carried out by teachers who act as facilitators and students as students and in the learning process there are media which function to attract students' interest in learning, especially in Islamic religious education. , for this reason it can encourage PAI teachers to be able to analyze their students, with the aim of increasing their interest in learning in PAI subjects. The aim of the researchers is to find out the implementation of learning media by PAI teachers in increasing student interest in learning at SDN 2 Wakan, and to find out Obstacles in implementing Learning Media by PAI Teachers in Increasing Student Interest in Learning at SDN 2 Wakan. The data collection techniques used were observation, interviews and documentation. The research results show that (1). There are various forms of implementing learning media, starting from print-based, visual-based, and also computer-based learning. (2). There are several obstacles to the implementation of learning media in interviews, such as the problem of monotonous media because it revolves around only those three media, student incompetence due to remote areas.